The Role of Electronic Records Management in Effective Service Delivery: A Case Study of Kabale District Local Government. - Asiimwe, Dianah (Kabale University, 2024)
The study covers the role of electronic records management in effective service delivery using Kabale district local government as the case study. The study was composed of five chapters whereby chapter one dealt with the background to the study, statement of the problem, purpose and objectives of the study, research questions, scope of the study, significance of the study, and definition of operational terms. Chapter two reviewed existing knowledge or literature review on the roles played by electronic records management in effective service delivery, challenges faced by electronic records management that hinder effective service delivery, possible solutions to challenges faced by electronic records management that hinder effective service delivery Chapter three presented the methodology used in the study. It describes the study area, research design, sample population and sample size, data collection instruments and tools, data processing, presentation, and limitations of the study. Chapter four presents the results of the study and findings from various respondents the researcher interacted with during data collection. Findings are organized and tabulated following the research objectives. Reporting of the findings was done in the form of a narrative discussion where the findings were first described and then analyzed. Chapter five presents the summary of findings conclusions, recommendations, limitations of the study, and areas for further research.